TAX AVOIDANCE DAN AUDIT REPORT LAG DI INDONESIA: TIPE AUDITOR INDEPENDEN SEBAGAI VARIABEL MODERASI - Theresia Cika Tanti Octa Paramita Clara (2022)
This study aims to determine the effect of tax avoidance on audit report lag with auditor type as a moderating variable in manufacturing companies in the goods and consumption sector listed on the Indonesia Stock Exchange. This research is a type of quantitative research that uses secondary data in the form of financial statement or company annual report. The sample in this study were 54 manufacturing and consumer goods companies. The data analysis technique in this study used a regression model selection test, classical assumption test, panel data regression, and partial hypothesis testing (t test). Based on the results of data analysis, it can be concluded that (1) tax avoidance has no significant effect on audit report lag, (2) the type of independent auditor does not strengthen the relationship between tax avoidance and audit report lag, and the control variables are (3) profitability has a significant effect on audit report lag, (4) leverage has no significant effect on audit report lag, and (5) firm size has no significant effect on audit report lag.